The Welfare Basis of Real Income Comparisons: A Reply - Sen, Amartya (Journal of Economic Literature, 1980)
IN PRESENTING his estimates of la richesse territoriale de France, Antoine Lavoisier [100, 1791] pointed out that the object of such estimation is to furnish a veritable thermometer of national prosperity.' That certainly has provided the motivation behind much work on national income estimation and comparison. Lavoisier was an optimist, and he felt that there need be little room for dispute if the problem were correctly posed and pursued: